2021
DOI: 10.3892/mmr.2021.12038
|View full text |Cite
|
Sign up to set email alerts
|

X‑irradiation induces acute and early term inflammatory responses in atherosclerosis‑prone ApoE‑/‑ mice and in endothelial cells

Abstract: Thoracic radiotherapy is an effective treatment for many types of cancer; however it is also associated with an increased risk of developing cardiovascular disease (CVD), appearing mainly ≥10 years after radiation exposure. The present study investigated acute and early term physiological and molecular changes in the cardiovascular system after ionizing radiation exposure. Female and male ApoE -/mice received a single exposure of low or high dose X-ray thoracic irradiation (0.1 and 10 Gy). The level of cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 98 publications
(130 reference statements)
1
6
0
Order By: Relevance
“…Interestingly we found that very low IR doses, from 0.005 Gy onwards, enhance sICAM levels in ApoE−/− mice and, at HDR only, also in wild type mice. These findings are in line with reports of low-dose IR induced acute upregulation of sICAM in ApoE−/− mice after thorax IR at 0.1 Gy [54]. Based on our previous investigations we assume that upregulation of ICAM after low-dose IR is only transient as it was even slightly counter-regulated after 3 months [28].…”
Section: Systemic In Vivo Responses After Whole Body Irradiation (Wbi)supporting
confidence: 93%
“…Interestingly we found that very low IR doses, from 0.005 Gy onwards, enhance sICAM levels in ApoE−/− mice and, at HDR only, also in wild type mice. These findings are in line with reports of low-dose IR induced acute upregulation of sICAM in ApoE−/− mice after thorax IR at 0.1 Gy [54]. Based on our previous investigations we assume that upregulation of ICAM after low-dose IR is only transient as it was even slightly counter-regulated after 3 months [28].…”
Section: Systemic In Vivo Responses After Whole Body Irradiation (Wbi)supporting
confidence: 93%
“…Wild type mice models are resistant to atherosclerosis development due to the low level of low-density lipoprotein (LDL), therefore, apolipoprotein E-deficient (ApoE−/−) mice and LDL receptor knock-out mice which display poor lipoprotein clearance with subsequent accumulation of cholesterol, that promote the development of atherosclerotic plaques, are the most common mice models to study the pathophysiology of atherosclerosis. We observed increased serum GDF-15 and CXCL10 in both female and male ApoE−/− mice at 24 h after low and high dose local thoracic irradiation, which was validated to be secreted from the coronary artery and microvascular endothelial cells in vitro (Ramadan et al 2021a , b ). GDF-15 and CXCL10 are proatherogenic inflammatory markers, and they are promising biomarkers in cardiovascular diseases in humans, including atherosclerosis (Xu et al 2011 ; Tavakolian Ferdousie et al 2017 ).…”
Section: Out-of-field Effects: Model Systems and Mechanismsmentioning
confidence: 75%
“…This macrovascular and microvascular damage could be triggered during thoracic radiotherapy by the scattered radiation doses received in the heart region, which may damage the endothelium directly, by inducing DNA damage, oxidative stress, cell death, inflammation, and premature cell senescence to initiate the atherosclerosis process, that may expand via bystander signaling to non-irradiated endothelial cells as shown in Fig. 1 (Ramadan et al 2021a , b ).
Fig.
…”
Section: Out-of-field Effects: Model Systems and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies in mice are expected to provide additional insights since the same mechanisms of arterial inflammation and oxidative stress have been implicated in IR-related vascular disease. However, in preclinical models, altered vascular reactivity, inflammation and oxidative stress have been reported within a few weeks after treatment 22-25 . Our experiments, conducted one year after IR, aimed to bridge the knowledge gap regarding long-term effects in preclinical models.…”
Section: Discussionmentioning
confidence: 99%